2021
DOI: 10.1007/s11136-021-02985-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of high adherence to vegetables and fruits dietary pattern with quality of life among Chinese women with early-stage breast cancer

Abstract: Purpose Dietary intake and patients’ quality of life (QoL) are important supportive care issues in breast cancer survivorship. This study aimed to identify dietary pattern before and after breast cancer diagnosis. In addition, the association between dietary patterns and QoL were cross-sectionally and longitudinally investigated. Methods A breast cancer cohort which included 1462 Chinese women were longitudinally interviewed at four time-points, namely bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…A Korean study showed that healthy eating habits improved dyspnea but increased insomnia in specific populations (11). A Chinese study investigated the relationship between eating more grain and animal products and poorer functions, including respiratory function and constipation, and the effects of a high-fruit and vegetable diet in improving quality of life, including physical, emotional, and cognitive functions, as well as reducing common gastrointestinal reactions, breathing problems, and insomnia (75).…”
Section: Unhealthy Dietary Patternsmentioning
confidence: 99%
“…A Korean study showed that healthy eating habits improved dyspnea but increased insomnia in specific populations (11). A Chinese study investigated the relationship between eating more grain and animal products and poorer functions, including respiratory function and constipation, and the effects of a high-fruit and vegetable diet in improving quality of life, including physical, emotional, and cognitive functions, as well as reducing common gastrointestinal reactions, breathing problems, and insomnia (75).…”
Section: Unhealthy Dietary Patternsmentioning
confidence: 99%
“…Furthermore, Lei et al have reported that dietary patterns involving a higher intake of grains and animal products are associated with poorer functioning in one's roles, while women who consume more fruits and vegetables have better QOL. This finding may be attributed to the ingredients involved in each of these dietary patterns, including refined grains, red and processed meat, and other foods with a high fat content ( 34 ). Demark-Wahnefried et al have reported that, among cancer survivors, a low-fat diet that is high in fruits and vegetables is associated with higher levels of physical functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have found that BC survivors who follow a better diet quality tend to experience less total fatigue, a common symptom among cancer patients. Consuming foods that are rich in anti-inflammatory nutrients such as n-3 PUFAs, vitamin C, carotenoids, and vitamin A has been associated with less persistent fatigue [280][281][282].…”
Section: Discussionmentioning
confidence: 99%